Resolution of Symptomatic Intracranial Hypertension Following Resection of Tentorial Meningioma Compressing the Dominant Transverse Sinus - Tomlinson, Samuel B.; Rahmani, Redi; Jabarkheel, Rashad; Kruszewski, Adam M.; Yoshor, Daniel; Srinivasan, Visish M. (Journal of Neurological Surgery Reports, 2025)
Symptomatic intracranial hypertension is a rare presentation of meningiomas associated with compression and/or invasion of the dural venous sinuses. Establishing a clear link between tumor-induced venous outflow obstruction and elevated intracranial pressure is essential to determine the appropriate management strategy.A 59-year-old female presented with headaches, imbalance, pulsatile tinnitus, and horizontal binocular diplopia secondary to bilateral abducens nerve dysfunction in the setting of a small tentorial meningioma compressing the dominant right transverse sinus. Venous manometry demonstrated elevated sinus pressures and a large pressure gradient across the lesion. Microsurgical resection improved the caliber of the transverse sinus and normalized intracranial pressures without the need for permanent venous stent placement.Tentorial meningiomas infrequently result in venous outflow obstruction and symptomatic intracranial hypertension. Thorough workup including diagnostic angiography, venous manometry, and temporary stenting can be used to confirm the diagnosis. Surgical resection with or without permanent stent placement can restore venous drainage and alleviate debilitating symptoms.
Keywords: tentorial meningioma; intracranial hypertension; venous manometry; venous outflow obstruction; elevated intracranial pressure; transverse sinus